Evolve: Language-Driven Engineering in Industrial Practice - Tegeler, Tim; Schürmann, Jonas (Electronic Communications of the EASST, 2020)
In general software projects still, have a very high failure rate. We noticed that one of our projects did not gather pace. It was delayed from the beginning and on the way to fail. After investigating the development process, we located the issue in the chosen architecture of the software. Although the used technology has many advantages, it handicapped the application developers by the cumbersome architecture. The challenge was how we could keep the advantages, but simplify the work of the application developers. We came up with the approach to build a toolkit and family of dedicated Domain-Specific Languages which is developed alongside the project. We called it Evolve, and it is built upon the Language-Driven Engineering paradigm. We were able to salvage the project and establish Evolve in the development process of related applications. With Evolve we successfully brought Language-Driven Engineering to industrial practice. It will play a major role in our future software development.